Biogeography of anaerobic ammonia-oxidizing (anammox) bacteria - Sonthiphand, Puntipar; Hall, Michael W.; Neufeld, Josh D. (Frontiers in Microbiology, 2014)
Anaerobic ammonia-oxidizing (anammox) bacteria are able to oxidize ammonia and reduce nitrite to produce N2 gas. After being discovered in a wastewater treatment plant (WWTP), anammox bacteria were subsequently characterized in natural environments, including marine, estuary, freshwater, and terrestrial habitats. Anammox bacteria play an important role in removing fixed N from both engineered and natural ecosystems, but broad scale anammox bacterial distributions, based on available data, have not yet been summarized. The objectives of this study were to explore global distributions and diversity of anammox bacteria and to identify factors that influence their biogeography. Over 6,000 anammox 16S rRNA gene sequences from the public database were analyzed in this current study. Data ordinations indicated that salinity was an important factor governing anammox bacterial distributions, with distinct populations inhabiting natural and engineered ecosystems. Gene phylogenies and rarefaction analysis demonstrated that freshwater environments and the marine water column harbored the highest and the lowest diversity of anammox bacteria, respectively. A co-occurrence network analysis indicated that Ca. Scalindua strongly correlated with other Ca. Scalindua taxa, whereas Ca. Brocadia co-occurred with taxa from both known and unknown anammox genera. Our survey provides a better understanding of ecological factors affecting anammox bacterial distributions and provides a comprehensive baseline for understanding the relationships among anammox communities in global environments.